The application of the capability approach to high-income OECD countries: A preliminary survey - Jürgen Volkert; Friedrich G. Schneider (Center for Economic Studies and ifo Institute (CESifo), 2011)
The goal of this paper is to provide a preliminary overview of empirical Capability Approach (CA) applications for high-income OECD countries. The survey aims at a basis of mutual exchange on relevant CA issues among researchers analyzing well-being in affluent countries. It focuses on CA applications related to general well-being, inequalities, poverty and human development in affluent countries. Based on this literature survey and an illustration of procedures and challenges of selecting relevant dimensions and referring to ongoing projects commissioned by the German and British government, the authors conclude that a stronger emphasis should be on assessing capabilities, autonomy, agency and responsibility.
Keywords: B41; I30; I31; I32; O15; 330; capability approach; high income countries; general well being; poverty; human development; assessing capabilities; Lebensqualität; Capability Approach; Sozialer Indikator; OECD-Staaten; Deutschland; Großbritannien